2010
DOI: 10.1111/j.1469-8986.2010.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortical dynamics during visuomotor transformation: Adaptation to a cognitive‐motor executive challenge

Abstract: EEG was employed during cognitive-motor adaptation to a visuomotor transformation that required inhibition of an established motor plan. Performance was positively related to frontal alpha and theta power during both planning and execution of reaching movements to visual targets. EEG changes suggest initial involvement of frontal executive functioning to suppress established visuomotor mappings followed by progressive idling (i.e., alpha synchrony). Also, progressive idling of the temporal and parietal sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 64 publications
11
65
0
Order By: Relevance
“…Most of these studies have focused on EEG spectral power and revealed a positive relationship between alpha power and expertise (e.g., Gentili, Bradberry, Hatfield, & Contreras-Vidal, 2008;Gentili et al, 2011;Hatfield, Landers, & Ray, 1984;Hatfield et al, 2004). In addition, some studies have reported contrasts of cortical network communications in novice and expert performers (Deeny, Haufler, Saffer, & Hatfield, 2009;Reiterer, Berger, Hemmelmann, & Rappelsberger, 2005).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most of these studies have focused on EEG spectral power and revealed a positive relationship between alpha power and expertise (e.g., Gentili, Bradberry, Hatfield, & Contreras-Vidal, 2008;Gentili et al, 2011;Hatfield, Landers, & Ray, 1984;Hatfield et al, 2004). In addition, some studies have reported contrasts of cortical network communications in novice and expert performers (Deeny, Haufler, Saffer, & Hatfield, 2009;Reiterer, Berger, Hemmelmann, & Rappelsberger, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Recently, the emergence of efficient cortical activity, as associated with a reduction in non-essential processing, was observed during the mastery of a task that required executive inhibition of a pre-existing motor plan (Gentili, Hadavi, Ayaz, Shewokis, & Contreras-Vidal, 2010;Gentili, Bradberry, Oh, Hatfield, & Contreras-Vidal, 2011;Gentili, Shewokis, Ayaz, & ContrerasVidal, 2013;Shadmehr & Holcomb, 1999). Although changes in regional activity supported the notion that psychomotor efficiency contributed to the improvement in performance of such cognitive-motor adaptation tasks, changes in cortical network communications were not examined.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…ERPCOH reflects coherent activity between distant areas that are engaged in a specific task. The degree of phase synchronization between two channels, thus, indicates reciprocal interactions between the participating neural populations (Engel et al 2001). In addition, to determine the variation of coherence as a function of the different stages of reaching, mean coherence estimates within each frequency band at selected channels were compared between the different time intervals of interest and the baseline (nonparametric t-test).…”
Section: Phase Coherence Changes Across Temporal Windowsmentioning
confidence: 99%
“…At the same time, there is some indication that the hypothesized endpoint control mechanism is expressed less consistently (Wang and Sainburg 2003); it is therefore possible that the abrupt and fairly large visual feedback perturbation attenuated or masked the left hand's proficiency for endpoint accuracy control and diminished the potential for interference here. It is interesting in this context to note that previous studies investigating brain dynamics during visuomotor adaptation have shown prefrontal inhibition during acquisition of a new internal model (Gentili et al 2011(Gentili et al , 2013; it is possible that such processes could contribute to a suppression of the nondominant hand's control strengths. Prefrontal cortical areas have also been shown to be involved in visuospatial planning (Basso et al 2006) and to receive projections from the anterior corpus callosum that are relevant for learning of bimanual coordination (Sisti et al 2012).…”
Section: Isodirectional Interferencementioning
confidence: 97%